Product Reviews in YouTube - Kim, Jiyeol; Rhee, Cheul (Asia Pacific Journal of Information Systems, 2020)
The outbreak of COVID-19 has changed our lifestyle. People spend much more time on YouTube, SNS and online shopping than before. Accordingly, the number of product review videos are steeply increasing in YouTube platform. When people watched the review videos, they might search additional information if they liked the videos. This study aims to investigate how the informativeness and the degree of attention gathering of product review videos influence on the product information sourcing intention and persuasion knowledge. We also try to find whether prior YouTube experience affects the relationship between the degree of attention gathering and persuasion knowledge. We conducted an online survey on 499 participants and analyzed using partial least square methods. Results show that 1) informativeness and the degree of attention gathering towards product review videos influence on the product information sourcing intention and user’s persuasion knowledge. 2) Viewers’ YouTube experiences moderate the increase of the viewers’ persuasion knowledge caused by increas- ing the degree of viewers’ attention gathering. This study implies that YouTube product review videos could be created in strategic manners. Also, it could be inferred that consumers’ prior YouTube experiences may reduce negative potentials of the degree of attention gathering onto persuasion knowledge.
Keywords: Informativeness; Persuasion Knowledge; Product Information Sourcing Intention; The Degree of Attention Gathering; YouTube Product Review